Increasing Diversity in Evolutionary Anthropological Sciences—the IDEAS Program. - Malhi, Ripan S.; Antón, Susan C.; Fuentes, Agustín (American Anthropologist, 2019)
The article discusses the Increasing Diversity in Evolutionary Anthropological Sciences (IDEAS) program supported by the American Association of Physical Anthropologists Committee on Diversity and funded by the National Science Foundation. Topics include the goal and main mentoring focus of the IDEAS program, result of reduced diversity in the biological anthropology research community and the disparity in representation of minority scholars in biological anthropology.